Case studies of low-performing college students with negative attitude towards physics - Veniegas, Andres L. (2009)
This study determined the characteristics of ten case-students who are low performing in, and with negative attitude towards, physics. It made us of observations, structure schedule interviews (SSI), as well as structured schedule interviews (USSI) of the subject cases, including their friends, relatives, and instructors, as the main data-gathering procedures. It was found that negative attitudes of the case-stdents towards Physics are primarily associated with the type of intelligence they possessed. Low performance and negative attitudes are also associated with poor foundations in Mathematics.